2007
DOI: 10.1029/2007ja012331
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Saturnian moons on Saturn kilometric radiation

Abstract: [1] Similar to past studies at Jupiter, we conduct an investigation of possible associations of radio emission occurrence probability with the orbital phases of Saturnian moons. We use a new definition of the Saturn longitude system (SLS) based on the results of Kurth et al. (2007). This paper presents results of our findings to date, sampling a large portion of the Radio and Plasma Wave Science (RPWS) instrument data over the frequency range 12 kHz < f < 16 MHz. We also investigate the intensity of Saturn kil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 37 publications
6
26
0
Order By: Relevance
“…In this paper we re-examine the occurrence probability of SKR emissions using a much larger database than the original study of Menietti et al (2007). We find the general conclusions of that study are confirmed.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…In this paper we re-examine the occurrence probability of SKR emissions using a much larger database than the original study of Menietti et al (2007). We find the general conclusions of that study are confirmed.…”
Section: Introductionsupporting
confidence: 59%
“…Jackman et al (2009) have shown the association of SKR radio emissions and plasmoid-like structures indicative of Saturn substorms. However, Menietti et al (2007) found no significant association of SKR emission with the orbital location of Enceladus, despite the known significant source of water ions associated with this moon (cf. Porco et al, 2006).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The frequent detection of the "extra" bursts also affirms that parameters other than planetary rotation and the solar wind conditions could affect the occurrence of SKR bursts, e.g. the location of Saturn's moons (Menietti et al, 2007) which appear to influence the occurrence of tail reconnection events (Russell et al, 2008). Kurth et al (2005a) discussed in depth event 3 mentioned above (25-31 January 2004, not shown here), when the SKR detections became very weak, and stated that although Cassini RPWS detected very little SKR emission, the Unified Radio and Plasma wave experiment onboard the Ulysses spacecraft did measure SKR at the expected time.…”
Section: Discussionmentioning
confidence: 99%
“…At Saturn, analogous footpoint emissions from Enceladus have been observed (Pryor et al 2011). Footpoint emissions associated with Titan have yet to be identified, however the motion of Titan itself has the potential for modulating Saturn's kilometric radiation (SKR)-a phenomenon which is associated with the auroral process (Menietti et al 2007).…”
Section: General Propertiesmentioning
confidence: 99%